Strengthening women in wheat farming in India: Old challenges, new realities, new opportunities - Farnworth, Cathy Rozel; Bharati, P.; Jafry, Tahseen; Badstue, Lone B. (International Maize and Wheat Improvement Center, 2018)
This resource provides guidance for scientists, researchers, and rural advisory services in wheat-based systems on how to better target women in all communities and how to improve inclusion for everyone. It builds on 12 case studies conducted across India’s wheat belt under CRP WHEAT. It discusses how norms are shifting in parts of rural India to accommodate open recognition of women as farmers and managers of wheat and as adopters of associated technologies, including zero tillers, combine harvesters, and improved varieties of wheat.